How will developmental neuroimaging contribute to the prediction of neurodevelopmental or psychiatric disorders? Challenges and opportunities - Koraly Pérez-Edgar; Mary Dozier; Rebecca Saxe; Katherine E. MacDuffie (Developmental Cognitive Neuroscience)
Successful developmental neuroimaging efforts require interdisciplinary expertise to ground scientific questions in knowledge of human development, modify and create technologies and data processing pipelines suited to the young brain, and ensure research procedures meet the needs and protect the interests of young children and their caregivers. This paper brings together four interdisciplinary perspectives to tackle a set of questions that are central for the field to address as we imagine a future role for developmental neuroimaging in the prediction of neurodevelopmental or psychiatric disorders: 1) How do we generate a strong evidence base for causality and clinical relevance? 2) How do we ensure the integrity of the data and support fair and wide access? 3) How can these technologies be implemented in the clinic? 4) What are the ethical obligations for neuroimaging researchers working with infants and young children?